A Pragmatic Analysis of Politeness Strategies in “Tenggelamnya Kapal Van der Wijck” - Ricky, Ricky; Afriana, Afriana (Prosiding, 2024)
Politeness is to convey an expression as pleasantly as possible, which is necessary to reduce conflict with others. As a result, being polite is essential because it allows people to express themselves without offending others. The aim of this study is to examine the strategies of politeness utilized in the movie "Tenggelamnya Kapal Van der Wijck" based on Brown and Levinson's theory (1987). This study employs a descriptive qualitative design in order to explain the many forms of politeness used by the characters in the film. According to the findings of this study, it found 14 occurrences spanning four categories of politeness strategies as defined by Brown and Levinson (1987). Specifically, the study found 4 cases of positive politeness, 3 instances of negative politeness, 4 instances of bald-on-record strategies, and 3 instances of off-record strategies. The politeness mentioned in the speech is beneficial, considering the film is about a cultural romance in a rural area of Indonesia.